Photon Characteristics and Behavior under Refractive Index (JOURNAL OF ADVANCES IN PHYSICS, 2022)
The effective mass, energy and momentum of photon in medium is described. The photon has both kinetic and potential energy and displays an effective mass when travelling through a medium. The photon is a type of elementary particle that serves as the quantum of the electromagnetic field and is explained through equations to have an elastic constant, volume, momentum, force, power and zero rest mass. The theory that photons a massless only applies to rest mass. A photon undergoes different dynamics such as strain and changes in effective mass under the influence of the refractive index that gives rise to a refractive force. This study synthesizes some properties of energy such as elastic constant, weight, and volume in order to explain the nature of photons and photon dynamics under refractive index. In this study, a helical spring model has been used to describe the behavior of a photon in the medium. The model connects together the exhibited properties such as energy, effective mass, spin, elastic constant and volume. Further explanation is given to the effect of gravitational force on wavelength and refractive index of air, and how gravitational force causes red and blue shifts in photon propagation. The quantization of energy has been extended to the quantization of space, time and matter. This study is consistent and consolidates the existing classical and quantum theories. There are further potential applications in optical communication, quantum cryptography, quantum optics, and medicine, especially in the use of two-photon excitation microscopy and photodynamic therapy.